Application of Tracer Isotope in Kinetic Study of First Order Ion Exchange Reaction - Lokhande, R.S.; Singare, P.U. (Asian Journal of Chemistry, 2010)
Analysis of fIrst order ion exchange reaction rates at differenttemperatures (27°-48°C) and particularly at low concentration ofpotassium iodide solution (electrolyte) ranging from 0.005 M to0.040 M is carried out by application of radioactive tracer isotope131I. With increase in concentration of electrolyte, amount of iodideion exchanged in millimoles increases. Specific reaction rates ofion exchange reaction are calculated for different temperatures andfor different amount of ion exchange resins. It is observed that withincrease in temperature, reaction rate increases but the increase ismore pronounced for increase in amount of ion exchange resins.For 0.005 M solution of electrolyte, the reaction rate increases from0.121 min-1 at 27°C to 178 min-1 at 48°C. For 0.005 M solutionof electrolyte, the reaction rate increases from 0.121 min-1 at 27°Cto 0.178 min-1 at 48°C. For 0.005 M solution of electrolyte at 27°Cthe reaction rate increases from 0.121 min-1 for 1.0 g of resin to0.368 min-1 for 5.0 g of resin. From the reaction rates calculatedat different temperatures, energy of activation in KJ/mole is calculated.It is observed that for 0.005 M solution of electrolyte, energyof activation is 4.62 kJ/mole which decreases to 2.87 kJ/mole forincrease in concentration of electrolyte to 0.100 M.